Incidence of Canine Appendicular Musculoskeletal Disorders in 16 Veterinary Teaching Hospitals from 1980 through 1989 - Johnson, Justine A.; Austin, Connie; Breur, Gert J. (Veterinary and Comparative Orthopaedics and Traumatology, 1994)
The goal of this study was to determine the incidence of musculoskeletal disorders in a large canine population. Patient information was obtained from clinical cases contributed to the Veterinary Medical Data Base (VMDB) by 16 veterinary teaching hospitals during the ten year period of 1980 through 1989. The relative contribution of bone diseases, joint diseases, and muscle-tendon-unit diseases was determined, and the incidence of each musculoskeletal disease reported.Nearly 24% of all patients in the source population had been affected by a disorder of the musculoskeletal system, and over 70% of those diagnoses involved appendicular structures. Diseases of joints, ligaments, and related structures contributed more cases (47%) to this study than diseases of bones (39%) or muscle-tendon-units (14%). Fractures made up the largest disease category, with pelvic fractures most common, followed by femoral fractures, and fractures of the radius and/or ulna. Joint instability and degenerative joint dis-ease were also common diagnosis categories, affecting primarily the hip and stifle joints. Common specific dis-ease entities included hip dysplasia, cruciate ligament rupture, traumatic hip luxation and patellar luxation.In this study we provided a comprehensive analysis of the canine musculoskeletal system. The relative importance of joint disorders compared to those of bones and muscle-tendon-units was illustrated. The incidence of most of the disorders described in this report had not been well documented previously.Patient information was obtained from the clinical cases of 16 veterinary teaching hospitals during a 10-year period. The number of dogs with musculoskeletal disorders was determined. The absolute and relative contribution of bone diseases, joint diseases, and muscle-tendon-unit diseases is reported as well as the incidence of the specific disease entities affecting the canine appendicular musculoskeletal system.
Keywords: Musculoskeletal; canine; epidemiology; bone; joint; muscle-tendon-unit